2017
DOI: 10.1017/s0033291717001490
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of longitudinal studies of cognition in bipolar disorder: comparison with healthy controls and schizophrenia

Abstract: Together with the findings in early BP and individuals at genetic risk for BP, current findings suggest that neurodevelopmental factors might play a significant role in cognitive deficits in BP and do not support the notion of progressive cognitive decline in most patients with BP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
93
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(108 citation statements)
references
References 80 publications
14
93
0
1
Order By: Relevance
“…Importantly, a recent meta‐analysis of the few published longitudinal studies of BD samples found no good evidence of decline in cognition over short (~1.5 years) or longer term (~5.5 years) periods . There was also no evidence for an effect of age, gender, education or changes in mood symptoms on cognitive change . Cognitive changes in BD patients also did not differ from healthy controls or SZ patients, and were largely consistent with an earlier meta‐analysis on the topic .…”
Section: Trajectory Of Cognitive Functioning In Bdsupporting
confidence: 72%
See 2 more Smart Citations
“…Importantly, a recent meta‐analysis of the few published longitudinal studies of BD samples found no good evidence of decline in cognition over short (~1.5 years) or longer term (~5.5 years) periods . There was also no evidence for an effect of age, gender, education or changes in mood symptoms on cognitive change . Cognitive changes in BD patients also did not differ from healthy controls or SZ patients, and were largely consistent with an earlier meta‐analysis on the topic .…”
Section: Trajectory Of Cognitive Functioning In Bdsupporting
confidence: 72%
“…Importantly, a recent meta‐analysis of the few published longitudinal studies of BD samples found no good evidence of decline in cognition over short (~1.5 years) or longer term (~5.5 years) periods . There was also no evidence for an effect of age, gender, education or changes in mood symptoms on cognitive change .…”
Section: Trajectory Of Cognitive Functioning In Bdmentioning
confidence: 95%
See 1 more Smart Citation
“…Conversely, most longitudinal studies have reported stability in neurocognitive deficits during a follow‐up period that ranged between 1 and 5 years . In fact, two meta‐analyses conducted on this subject have reported stability in neurocognitive performance among middle‐life BD subjects . Nonetheless, it remains plausible that deterioration in neurocognitive performance might occur in very early or late stages of the course of this disease, and meta‐analyses conducted on middle‐life patients (or averaging over patients across all stages) were unable to detect these processes.…”
Section: Introductionmentioning
confidence: 85%
“…However, not all longitudinal studies of cognitive functioning in bipolar disorder support the notion of deteriorating cognitive functioning over the course of the disorder. Several studies have observed static cognitive deficit trajectories in the bipolar disorder (Samame et al 2014; Bora and Ozerdem 2017; Martino et al 2018), and several studies demonstrate cognitive improvements after the first manic episode (Torres et al 2014; Torrent et al 2018). It is also plausible that premorbid cognitive functioning impairments in bipolar disorder are associated with specific genetic variants (Arts et al 2013; Bryzgalov et al 2018; Flowers et al 2016) that may be associated with neural development (Tabares-Seisdedos et al 2008) and thus may not be present in all individuals premorbidly.…”
Section: Introductionmentioning
confidence: 99%